2010
DOI: 10.1017/s1446788710001473
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Generating Sets for Direct Powers of Classical Algebraic Structures

Abstract: Communicated by M. G. JacksonDedicated to the memory of Jim Wiegold. AbstractFor an algebraic structure A denote by d( A) the smallest size of a generating set for A, and let, where A n denotes a direct power of A. In this paper we investigate the asymptotic behaviour of the sequence d( A) when A is one of the classical structures-a group, ring, module, algebra or Lie algebra. We show that if A is finite then d( A) grows either linearly or logarithmically. In the infinite case constant growth becomes another p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…James Wiegold proved in [7] that the growth rate of a finite perfect group is logarithmic (d A (n) ∈ Θ(log(n))), and that the growth rate of a finite imperfect group is linear (d A (n) ∈ Θ(n)). This result, herein called Wiegold dichotomy, was extended by Martyn Quick and Nik Ruškuc in [6] to several kinds of algebras that have underlying group structure. Namely, Quick and Ruškuc showed that a finite algebra A satisfies d A (n) ∈ Θ(log(n)) if A is a perfect ring, module, Lie algebra or k-algebra over a field k, and that d A (n) ∈ Θ(n) if A is an imperfect algebra of one of these types.…”
Section: Introductionmentioning
confidence: 88%
“…James Wiegold proved in [7] that the growth rate of a finite perfect group is logarithmic (d A (n) ∈ Θ(log(n))), and that the growth rate of a finite imperfect group is linear (d A (n) ∈ Θ(n)). This result, herein called Wiegold dichotomy, was extended by Martyn Quick and Nik Ruškuc in [6] to several kinds of algebras that have underlying group structure. Namely, Quick and Ruškuc showed that a finite algebra A satisfies d A (n) ∈ Θ(log(n)) if A is a perfect ring, module, Lie algebra or k-algebra over a field k, and that d A (n) ∈ Θ(n) if A is an imperfect algebra of one of these types.…”
Section: Introductionmentioning
confidence: 88%
“…What is really proved in [29] is that if Σ Grp is the set of identities axiomatizing the variety of groups and A is a finite algebra realizing Σ Grp , then A has a logarithmic growth rate if it is perfect and has a linear growth rate if it is imperfect. Although the results of [29] are stated for only a few specific varieties of group expansions, the results hold for any variety of group expansions.…”
Section: Non-hopf Kernelsmentioning
confidence: 99%
“…Our work. We got interested in growth rates of finite algebras after reading [28,Remark 4.15], which states that At present no finite algebraic structure is known for which the d-sequence does not have one of logarithmic, linear or exponential growth. We found some of these missing algebras (Theorem 5.10).…”
Section: Non-hopf Kernelsmentioning
confidence: 99%
“…In order to establish various examples of semigroups without identity, as required for (IG7)-(IG9), we utilise a construction introduced in [9] as a modification of an earlier construction by Byleen [2]. Let A and B be two (disjoint) countably infinite alphabets.…”
Section: Semigroups With Slowly Growing D-sequencesmentioning
confidence: 99%
“…The results from above concerning groups largely carry over to other 'classical' algebraic structures, such as rings, associative and Lie algebras; this is the topic of [9]. The purpose of the present article is to present some results concerning the growth of d(S) for an infinite semigroup or monoid S. We mention in passing that recently d-sequences have (re)appeared in the context of Universal Algebra, in connection with quantified constraint satisfaction problems; see [5].…”
Section: Introductionmentioning
confidence: 99%